Quṣayr ʻAmra : art and the Umayyad elite in late antique Syria - Fowden, Garth (Transformation of the classical heritage, 2004)
The remarkable frescoes of Quṣayr ʻAmra were probably painted in the middle of the 8th century for a Muslim Arab prince. However many problems remain with regard to the date, the patron & even the meaning of the often erotic scenes. Garth Fowden explores this treasure from the Syrian Desert.